Ornamental Throat Feathers Predict Telomere Dynamic and Hatching Success in Spotless Starling (Sturnus unicolor) Males - Azcárate-García, Manuel; Ruiz-Rodríguez, Magdalena; Díaz-Lora, Silvia; Ruiz-Castellano, Cristina; Martín-Vivaldi, Manuel; Figuerola, Jordi; Martínez-de la Puente, Josué; Tomás, Gustavo; Pérez-Contreras, Tomás; Soler, Juan José (Frontiers in Ecology and Evolution, 2020)
Sexually selected signals reliably reflect individual phenotypic or genetic quality and, thus, survival prospects of holders. Telomere length is considered a good predictor of life expectancy and, consequently, exploring the links between telomere length and sexually selected traits is much needed to better understand the mechanisms that maintain the honesty of sexual signals. We manipulated the length of throat feathers in spotless starling (Sturnus unicolor) males (a sexually selected signal) before reproduction and explored its effects on telomere shortening and breeding performance in subsequent reproductive events. We did not detect an effect of the feathers clipping manipulation, but males with longer throat feathers before the experiment had shorter telomeres that also shortened more slowly than those of males with shorter throat feathers did. Moreover, length of throat feathers of males before manipulation was positively related to hatching success of second clutches. Thus, correlative but not experimental results support the expected associations between sexually selected signals, telomeres and reproduction. We discuss such results in scenarios of sexual selection where feather length reflects, but does not directly cause, telomere attrition and enhanced reproductive success. Males with longer throat feathers might be older, more experienced males (i.e., with shorter telomeres), able to buffer telomere shortening between reproductive events. Because of the absence of experimental effects, differential incubation effort of females cannot explain the detected association with hatching success, but other sexually selected traits that covary with throat-feather length could be responsible. Exploring those physiological and/or morphological characteristics related to throat-feather length should therefore be the matter of future research.